PENGEMBANGAN TARI TOPI DALAM MENINGKATKAN KEMAMPUAN FISIK MOTORIK ANAK RA TUNAS BANGSA SIDOGEMAH SAYUNG DEMAK - Miftahun Ni’mah; Fu’ad Arif Noor (QURROTI, 2022)
This study aims to determine the application of the Hat Dance to the children of Group B RA Tunas Bangsa Sidogemah Sayung Demak and to determine the increase in gross motor skills of children with the Hat Dance method in group B children of RA Tunas Bangsa Sidogemah Sayung Demak. Data collection techniques in this study through observation and documentation techniques. This type of research is classroom action research with qualitative descriptive data analysis. The subjects used were students of RA Tunas Bangsa Sidogemah Sayung Demak with a population of 27 children. Sources of data come from educators and education staff. The results of this study indicate that there is an increase in children's physical motor skills through the Hat Dance media based on data on the pre-action aspects of flexibility from 48.14% then increased in Cycle I to 74.07% and Cycle II increased to 98.14%. In the pre-action, the agility aspect increased from 42.59%, in Cycle I it became 79.62% and in Cycle II it increased to 99.07%. In the pre-action, the balance aspect increased from 40.74% then increased, Cycle I became 62.96% and Cycle II increased to 97.22%. From these data, it can be concluded that the hat dance activity can improve the gross motor skills of class B children of RA Tunas Bangsa Sidogemah. This is because the hat dance dance activity can stimulate children's motor development in terms of flexibility, agility and balance.